2022
DOI: 10.1371/journal.pone.0269015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intensification of religious involvement during the COVID-19 pandemic in Poland

Abstract: Introduction The emergence of the virus Sars-CoV-2, and subsequent COVID-19 pandemic, caused a global threat to public health. In such challenging and worrying situations it can be expected that people will seek comfort in religion. However, before the pandemic there were never such wide world disruptions of religious practice–because of social distancing regulations, religiosity cannot be practiced in the same way as it was before the pandemic. Methods Two anonymous online surveys were conducted of adult Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In the period between 2018 and 2021 alone, the percentage of respondents who regularly practice religion decreased by 11 percentage points, while the number of nonpracticing individuals increased by 14 percentage points (from 35% to 49%). These trends are consistent with the results of other studies carried out in Poland, which indicate the impact of the pandemic on the decline in religious commitment and suggest the polarization of religiosity (Bożewicz 2022;Bożewicz and Boguszewski 2021;Boguszewski, Makowska and Podkowińska et al 2022).…”
Section: Religiousness Of Polish Youth -Changes Over Timesupporting
confidence: 91%
“…In the period between 2018 and 2021 alone, the percentage of respondents who regularly practice religion decreased by 11 percentage points, while the number of nonpracticing individuals increased by 14 percentage points (from 35% to 49%). These trends are consistent with the results of other studies carried out in Poland, which indicate the impact of the pandemic on the decline in religious commitment and suggest the polarization of religiosity (Bożewicz 2022;Bożewicz and Boguszewski 2021;Boguszewski, Makowska and Podkowińska et al 2022).…”
Section: Religiousness Of Polish Youth -Changes Over Timesupporting
confidence: 91%
“…In relation to the COVID-19 pandemic, studies have shown that women were more likely than men to attend mass, say prayers, and were more enthusiastic about national leadership and local churches ( Meza, 2020 ; Francis & Village, 2022 ). Interestingly, a study conducted among Poles during the COVID-19 pandemic showed no statistical significance with regard to the correlation between gender and religious commitment ( Boguszewski, Makowska & Podkowińska, 2022 ). In addition, statistical analysis showed that women for whom religion is important rated the quality of healthcare services higher before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%